Load activated FGFR and beta1 integrins target distinct chondrocyte mechano-response genes - Dietmar, Helen; Weidmann, Pia; Alberton, Paolo; Teichwart, Terrilyn; Gerstner, Matthias; Renkawitz, Tobias; Vortkamp, Andrea; Aszodi, Attila; Richter, Wiltrud; Diederichs, Solvig (Matrix biology, 2025)
In response to mechanical stimuli, chondrocytes adapt their transcriptional activity, thereby shaping the cellular mechano-response; however, it remains unclear whether the activation of cell surface receptors during mechanical loading converge in the activation of the same mechano-response genes, or whether pathway-specific genes can be defined. We aimed to determine whether load-activated FGF/FGFR signalling and β1 integrins activate ERK and control the same or distinct subsets of mechano-regulated genes. To this end, tissue-engineered neocartilage was generated from murine costal chondrocytes or human articular chondrocytes and subjected to dynamic unconfined compression with or without FGFR inhibition. To assess the role of β1 integrins, neocartilage was generated from embryonic β1 integrin-deficient or wild type costal chondrocytes. Load-activated FGFR signalling drove ERK activation in murine chondrocytes, and partially also in human chondrocytes, and mechano-response genes could be classified according to their regulation: Fosl1, Itga5, Ngf and Timp1 were regulated by load-activated FGFR depending on the developmental stage, whereas β1 integrins controlled Inhba expression. In human chondrocytes, load-activated FGFR signalling controlled expression of BMP2, PTGS2 and DUSP5, but not FOSB. We show here that the chondrocyte loading response is coordinated by concurrent activation of multiple receptors, and identified for the first time distinct target genes of activated receptors. These insights open up the opportunity to pharmacologically shape the mechano-response of chondrocytes in future studies with promising implications for the management of osteoarthritis and the development of novel therapeutic strategies.
Online verfügbar: 14. Mai 2025, Artikelversion: 24. Mai 2025
Gesehen am 15.09.2025